Weed Control Efficiencies, Grain Yield and Economics as Affected by Seedbed Preparation and Weed Management Practices in Central Terai, Nepal - Karki, Tika Bahadur; Gyawaly, Pankaj; Sah, Shrawan Kumar; Marahatta, Santosh; Gyawaly, Chetan (Agronomy Journal of Nepal, 2022)
Grain yield under dry direct seeded rice (DDSR) is primarily limited due to weeds. Therefore, a field experiment was conducted at Rampur, Chitwan during the monsoon season, of 2014. The treatments consisted of two methods of seedbed preparation in the main plot and six weed management methods in the sub-plot arranged in split plot design with four replications. Results revealed that the grain yield of dry-direct seeded rice did not vary due to seedbed preparation methods. However, weedy check treatments reduced more than 92.78 % of grain yield of dry-direct seeded rice compared to weed-free check. The herbicidal treatments were found to be superior for the benefit-cost ratio. Pendimethalin fb Bispyribac sodium recorded the highest net returns of NRs 68.73 thousand ha-1 and the benefit-cost ratio of 2.55. Sequential application of Pendimethalin followed by Bispyribac sodium was proved to be the most efficient weed management method for dry-direct seeded rice.